New evaluation method for the characterization of coatings by electroerosive alloying. (1st March 2023) - Zhengchuan, Zhang; Tarelnyk, Viacheslav; Konoplianchenko, Ievgen; Guanjun, Liu; Hongyue, Wang; Xin, Du; Yao, Ju; Zongxi, Li
Abstract: The running-in coatings were formed on the surface of tin bronze QSn10-1 by electroerosive alloying (EEA) with soft antifriction materials such as silver, copper, Babbitt B83 and graphene oxide (GO). The mass transfer, surface roughness, coating thickness and dry friction coefficient of the running-in coatings were measured and analyzed by a precision electronic balance, three-dimensional optical profiler, metallographic microscope, scanning electron microscope (SEM), energy dispersive spectrometer (EDS) and friction and wear tester. An evaluation indicator system for the characterization was constructed based on six factors, including material price, time, mass transfer, roughness, thickness and friction coefficient of the coatings by electroerosive alloying. The Shannon entropy method was used to calculate the weight of different indices, and a comprehensive evaluation method for running-in coatings performance was proposed by combining the technique for order preference by similarity to ideal solution (TOPSIS) and a multicriteria decision-making technique. The TOPSIS model was employed for the comprehensive evaluation ranking of the characterization of the running-in coatings by electroerosive alloying.